Directly targeting PRDM16 in thermogenic adipose tissue to treat obesity and its related metabolic diseases - Mao, Liufeng; Lu, Jinli; Hou, Yunliang; Nie, Tao (Frontiers in Endocrinology, 2024)
Obesity is increasing globally and is closely associated with a range of metabolic disorders, including metabolic associated fatty liver disease, diabetes, and cardiovascular diseases. An effective strategy to combat obesity involves stimulating brown and beige adipocyte thermogenesis, which significantly enhances energy expenditure. Recent research has underscored the vital role of PRDM16 in the development and functionality of thermogenic adipocytes. Consequently, PRDM16 has been identified as a potential therapeutic target for obesity and its related metabolic disorders. This review comprehensively examines various studies that focus on combating obesity by directly targeting PRDM16 in adipose tissue.